1973
DOI: 10.1136/jcp.26.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Identification of crystals deposited in brain and kidney after xylitol administration by biochemical, histochemical, and electron diffraction methods

Abstract: The positive identification of crystals of calcium oxalate occurring in brain and kidney after xylitol administration is described. Biochemical, histochemical, conventional light and electron microscopical methods, including selected area electron diffraction, were used to characterize the crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1975
1975
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Acidosis is followed by deteriorating renal function and death. Oxalate crystals have been demonstrated in the kidney and brain of patients dying in this way (Evans et al, 1973;Schroder et al, 1974). More recent studies have suggested that patients with renal failure who are infused rapidly with large doses of xylitol are unable to excrete the large amounts of glycolic acid formed.…”
Section: Acquired Oxalosismentioning
confidence: 99%
See 2 more Smart Citations
“…Acidosis is followed by deteriorating renal function and death. Oxalate crystals have been demonstrated in the kidney and brain of patients dying in this way (Evans et al, 1973;Schroder et al, 1974). More recent studies have suggested that patients with renal failure who are infused rapidly with large doses of xylitol are unable to excrete the large amounts of glycolic acid formed.…”
Section: Acquired Oxalosismentioning
confidence: 99%
“…Various sophisticated techniques such as x-ray diffraction, electron microprobe, and chromatography have all been used to identify calcium oxalate derived from histological material (Bennett and Rosenblum, 1961;Bennington et al, 1964;Evans et al, 1973). Facilities for such techniques are not always readily available, while the random orientation and fragmentation of the crystals create difficulties in their application.…”
Section: (B) Histological Characterisation Of Calcium Oxalatementioning
confidence: 99%
See 1 more Smart Citation
“…During the past 30 years several cases of fatal reactions following xylitol infusion have been reported (Evans et al 1973;Schultze et al 1983;Frydl 1987;Bergmann et al 1991;Heye et al 1991;Leidig et al 2001). In all cases the most striking abnormality was the presence of birefringent crystalline material in the tubules of the kidneys.…”
Section: Introductionmentioning
confidence: 94%
“…Different toxicities associated with nonglucose carbohydrates have been observed. Xylitol overdose has caused a few cases of deposits of oxalate crystals in the kidney and brain (Evans et al, 1973;Heye et al, 1991). Administration of large amounts of fructose or xylitol can produce lactic acidosis (Leutenegger et al, 1977;Ladefoged et al, 1982;Danahoe & Powers, 1970).…”
Section: Discussionmentioning
confidence: 99%